Kajian Bentuk dan Makna Simbolik Figurin Gerabah Majapahit (Periode Hayam Wuruk 1350-1389 M) - Anne Susannawaty (ITB Journal Publisher, LPPM ITB, 2008)
The earthware figurines of Majapahit were clay-based artworks from the Majapahit Kingdom (1350-1389 AD) of Trowulan at Mojokerto, East Java. The name